A case of leptospirosis in a child with unusual clinical manifestation - Biswas, A; Kumar, R; Chaterjee, A; Pan, A (Journal of College of Medical Sciences-Nepal, 2012)
Leptospirosis is a re-emerging zoonotic disease with a worldwide distribution. In the mild form it may present as flu like illness. Severe form characterized by jaundice, renal dysfunction and hemorrhagic diathesis is referred to as Weil’s syndrome. Very few cases have been reported in India, and pediatric cases are extremely rare. We report a case of leptospirosis in a 12 year old girl who presented with irregular fever, malaise and spontaneous bleeding from nose. She also had headache, vomiting, subconjunctival hemorrhage, photophobia, pain abdomen, cervical lymphadenopathy, myalgia, and arthralgia. She developed severe coagulopathy, bilateral pleural effusion, ascitis, acalculous cholecystitis ultimately leading to ARDS and later multi-organ failure. ELISA for IgM leptospira was sent which came to be positive. She was given several units of packed cell, platelet concentrate, and plasma transfusion, and later mechanical ventilation and inotropic support. The patient was put on intravenous penicillin G.. which was continued for 10 days. Three weeks following admission, she had made a complete recovery and was discharged. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 37-41 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6836